Intelligent power monitoring and control with wireless sensor network techniques - Iman Mohammed Nayyef; Anas Ali Hussien (Institute of Advanced Engineering and Science, 2020)
Undoubtedly, there is a necessity for establishing a more intelligent power system in the existing energy system, which is increased according to the development of wireless system network (WSN) and the Internet of Things (IoT). This study presents intelligent power monitoring and control with wireless sensor network techniques, based on WSNs and IoT technologies is designed to manage real-time power at buildings. This system includes a complete network of wireless sensing node, base station and a smart home gateway. A sensing node is utilized as wireless sensors to measure voltage and current and to calculate power consumption of connected appliances that are transmitted wirelessly to a base station via Zigbee node. A base station is designed to receive all data transmitted from the sensing node and display it through GUI available at the personal computer with the possibility of controlling ON and OFF appliances according to consumer requirements. All of these readings are stored at database for analysis. In addition, a smart home gateway is used to connect the system with internet, allowing consumers to continuous monitoring and remote control the appliances via a smartphone application. The benefit of this system is that the mechanism of appliances control can be done in different ways (manually, automatically and remotely). To ensure better accuracy of the equipment many appliances are tested and compared with practical measurement. Best results are obtained for the error, voltage, current and the power.